Матеріали буго-дністровської неолітичної культури долини Дністра в межах України - Гаскевич, Д.Л. (Археологія і давня історія України, 2018)
Зібрано та проаналізовано відомості про пам'ятки Середнього Подністер'я зі знахідками, віднесеними до буго-дністровської культури. Опубліковано неолітичні матеріали з чотирьох пунктів,
колекції яких зберігаються в Наукових фондах Інституту археології НАН України. A review of the available records on the Early Neolithic in the Dnister River basin leads one to conclude
that referring the finds from several sites situated at the territory of the Chernivtsi region of Ukraine to the
Buh-Dnister Culture (BDC) is disputable. Information about some of them is absent in publications. Published
data about the others is fragmentary. In such a situation major attention has to be paid to the sources
of primary information — field documentation and collections of finds. Careful examination of materials from the Middle
Dnister area sites, stored at the Institute of Archaeology, NASU, has confirmed that a few potsherds from
the Trypillia B I settlement of Vasylivka and the multilayered site of HES-15 belong to the BDC. Drawings
of these potteries have been published in the article for the first time. Today, they should be considered as the
westernmost confirmed evidence of the BDC. The flint artefacts found close to the pottery typologically can be
attributed to either the Neolithic and Chalcolithic or to the both periods. Such position of BDC and Trypillian
finds at one depth is well established in some other sites of the Dnister River area. For example, it was
testified by the author’s excavation at the well known Buh-Dnister settlement of Tsekynivka I in 2010.
Belonging of the site of Hordivtsi to the BDC can be neither proved, nor disproved on the basis of materials
available in Kyiv. Among surface finds collected there by the author in 2005 and 2009, there is only one diagnostic
potsherd of evident Neolithic age. It is a bottom of the vessel more typical for wares of the local variant of the Criş
culture or Prut-Danube network, after Agathe Reingruber, and less common for both Buh-Dnister and the early
Trypillian pottery. Consequently, a cultural attribution of Hordivtsi and a few other Neolithic sites located near
the Dnister River to the west of HES-15 requires a study of finds discovered there in the 1950s and stored at the
I. Krypiakevych Institute of Ukrainian Studies, NAS of Ukraine in Lviv, as well as running a new field research.